Functions and Roles of Industrial Relations Mediators at the Department of Manpower in Makassar City - Zulfachry Zulfachry; Zul Fadli; Wahyuddin S; Zul Rachmat (Universitas Negeri Makassar, 2022)
Competence is an ability that must be possessed by an Industrial Relations Mediator. Because of the competence of an officer, he will be able to carry out work in his field of duty and be able to complete the task with good and correct results. Based on this description, the purpose of this study is to find out and analyze more deeply about the Competence of Industrial Relations Mediators at the Makassar City Manpower Office. This research method uses descriptive qualitative. The informants were as many as nine people. Data collection techniques and instruments with interviews, observations and document reviews. Data analysis techniques by collecting data, reducing data, displaying data, verifying and drawing conclusions. The results showed that the competence of industrial relations mediators in terms of skill aspects is categorized well based on two indicators, namely technical skills and human skills. From the aspect of knowledge is categorized both based on indicators of educational background and disciplines owned by a fairly high Mediator of Induatrial Relations. From the aspect of self-image/attitude, it is categorized as quite good, based on two indicators, namely self-control, the Industrial Relations Mediator is good but from the self-confidence indicator when viewed from the work team, it is good but when viewed from the personal is still inadequate.